Traceability of Biologics in The Netherlands: An Analysis of Information-Recording Systems in Clinical Practice and Spontaneous ADR Reports - Klein, Kevin; Scholl, Joep H. G.; Vermeer, Niels S.; Broekmans, André W.; Van Puijenbroek, Eugène P.; De Bruin, Marie L.; Stolk, Pieter (Drug safety, 2016)
Introduction and Objective Pharmacovigilance requirements for biologics mandate that EU Member States shall ensure that any biologic that is the subject of a suspected adverse drug reaction (ADR) is identifiable by brand name and batch number. Recent studies showed that brand name identification is well established, whereas batch numbers are (still) poorly reported. We evaluated information-recording systems and practices in the Dutch hospital setting to identify determinants for brand name and batch number recording as well as success factors and bottlenecks for traceability. Methods We surveyed Dutch hospital pharmacists with an online questionnaire on systems and practices in hospitals for recording brand names and batch numbers. Additionally, we performed an analysis of the traceability of recombinant biologics in spontaneous ADR reports (received between 2009 and 2014) from the Netherlands Pharmacovigilance Centre Lareb. Results The survey showed that brand names are not routinely recorded in the clinical practice of Dutch hospitals, whereas batch numbers are poorly recorded. Seventy-six percent of the 1523 ADR reports for recombinant biologics had a traceable brand name whereas 5 % of these reports contained a batch number. The results suggest a possible relationship between the availability of brand and batch number information in clinical practice and the inclusion of this information in ADR reports for biologics. Conclusion The limited traceability of brand names and batch numbers in ADR reports may be primarily caused by the shortcomings in the recording of information in clinical practice. We recommend efforts to improve information-recording systems as a first step to improve the traceability of biologics in ADR reporting.